2018
DOI: 10.13075/mp.5893.00687
|View full text |Cite
|
Sign up to set email alerts
|

Simplicity or complexity of the radiopharmaceutical production process in the light of optimization of radiation protection of staff – <sup>99m</sup>Tc vs. <sup>18</sup>F

Abstract: The simplicity of obtaining the 99mTc isotope as well as the complex, but fully automated production process of the 18F-FDG radiopharmaceutical optimize the radiation protection of workers, excluding manual procedures labelling with 99mTc or quality control of 18F-FDG. Med Pr 2018;69(3):317–327.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 18 publications
0
8
0
Order By: Relevance
“…Previously, the authors of the present study have already investigated hand exposures due to the most popular radionuclide, 99m Tc, produced with a radionuclide generator (Wrzesień 2018). It is worth noting that compared with 18 F or 68 Ga, 99m Tc is a source of gamma radiation with an energy of 144 keV.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…Previously, the authors of the present study have already investigated hand exposures due to the most popular radionuclide, 99m Tc, produced with a radionuclide generator (Wrzesień 2018). It is worth noting that compared with 18 F or 68 Ga, 99m Tc is a source of gamma radiation with an energy of 144 keV.…”
Section: Discussionmentioning
confidence: 98%
“…This is because employees typically do not only carry out the procedures of producing the radionuclides by themselves, but also label chemical compounds with these radionuclides in order to obtain radiopharmaceuticals, and/or inject the prepared radiopharmaceutical into a patient's body (Stuarto 1990;Chiesa et al 1997;Williams et al 1990;Batchelor et al 1991;Dhanse et al 2000;Kubo & Mauricio 2014;Sandouqa et al 2011;Leide-Svegborn 2011). The occupational groups most affected by this exposure are radiochemists and nurses (Meisenheimer et al 2020;Wrzesień and Napolska 2015;Wrzesień et al 2019;Wrzesień and Albiniak 2016;Wrzesień 2018;Vanhavere et al 2012). During the last decade, a lot of attention in scientific publications has been devoted to the exposure of the hands when performing tasks involving radionuclides (Sans-Merce et al 2011a;Breeman et al 2005;Wrzesień et al 2008;Carnicer et al 2011;Sans Merce et al 2011b).…”
Section: Introductionmentioning
confidence: 99%
“…The first was the choice of the hand model. For this it was important to realize that dosimetry measurements suggested that the quality control procedure and radiopharmaceutical injection have the greatest impact on the dose to the fingertips of personnel (Wrzesień et al 2016 , 2018 ; Wrzesień 2018a , b ). Taking into account the fact that 70% of employees performing the above-mentioned procedures are women, the dimensions of the female hand model were used to construct the hand model.…”
Section: Methodsmentioning
confidence: 99%
“…The measurements included highly sensitive MCP-N (LiF: Mg, Cu, P) thermoluminescence detectors manufactured by Radcard (Kraków, Poland). The detectors were calibrated in accordance with ISO 4037-3 (ISO 2019 ) as described in (Wrzesień et al 2016 , 2018 ; Wrzesień 2018a , b ; Wrzesień and Napolska 2015 ). In total, 22 workers were included in the dosimetry measurements, including four physicists, nine chemists and nine nurses.…”
Section: Methodsmentioning
confidence: 99%
“…Tc‐99m is the most used radionuclide in nuclear medicine imaging because it fulfills many of the criteria of an ideal radionuclide, such as half‐life, decay mode, and photon energy. 1 , 2 , 3 In our routine practice, scintigraphic exams using Tc‐99m radiolabeled pharmaceuticals are usually acquired with a low‐energy high‐resolution (LEHR) collimator. 4 , 5 Collimator design is a compromise between spatial resolution and sensitivity.…”
Section: Introductionmentioning
confidence: 99%